Kearifan Lokal dalam Pendidikan Moderasi Beragama: Telaah Nilai Filosofis Makna Simbolik Tepak Sirih - Dawami, Dawami; Akbar, Muhammad Rizal; Nurmatias, Windayani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study Abstract: This study aims to explore the philosophical meaning of Tepak Sirih as a representation of local Malay wisdom in supporting the values of religious moderation. Religious moderation is often understood in normative terms, but it has rarely been examined from the perspective of local culture. This study addresses that gap by investigating the symbolic meanings of the elements within Tepak Sirih—such as betel leaves (sirih), areca nut (pinang), lime (kapur), and gambier (gambir)—which reflect values of tolerance, respect, and balance. A descriptive qualitative method with a hermeneutic approach was used to interpret cultural meanings in the context of religiosity. The findings show that Tepak Sirih is not only a cultural heritage artifact but also serves as an educational medium in shaping moderate religious attitudes. This study contributes new insights to the discourse on religious moderation based on local culture and is recommended for integration into multicultural and religious education.